Rethoric and agency around Iberian sacred landscapes (11th and 12th centuries) - Consiglieri, Nadia Mariana (2018)
This paper aims to demonstrate the feasibility of referring to ‘landscapes’ in medieval art. To this end, it will focus on the agency and rhetoric of five Iberian landscape representations produced between the eleventh and the twelfth centuries. These are the Girona Creation Tapestry, folios 63v-64r and 186v-187r of the Facundus Beatus, the wall paintings of the Pantheon of the Kings, the Monastery of Santa María de Sigena, and the Church of Santa María de Taüll. Do they reflect a direct observation of reality? To what extent are these landscapes symbolic and are their figures acting as spatial references cores? They show a rhetorical selection of points of view working as visual mediums. The notion of space is accentuated as an abstraction, a scenery of social practices and Biblical locations. This inquiry opens the discussion about the role of the multiple devices through which Romanesque landscapes were expressed.